The knowledge and skills on pediatric EEG in medical education - Lublin experience - Golebiowska, Maria; Golebiowska, Beata; Zienkiewicz, Ewa (Journal of Education, Health and Sport, 2018)
Background Electroencephalography is a study that records the electrical activity of the cerebral cortex. This record of neuronal communication supports clinical diagnosis of epilepsy and status epilepticus and monitoring of its future courses. That is why electroencephalography is considered one of the most important examination in children neurology. Aim and methodology Due to the interest of medical students in neuroscience, the Pediatric EEG Training was conducted and its efficacy was measured. The study group included 68 international students, who attended lectures in 10-15 participant groups in year 2014-2017. Both knowledge and students self-confidence were rated before and after conduction of the workshops. Results After the conduction of the workshop, 73% increase of knowledge was observed. In aspect of self confidence, 91% of participants confirmed they are confident in reasonable ordering of the examination to their future patients, and 72% of participants feel confident in technical preparation of the examination. Small groups of participants and sufficient amount of time for both theoretical lecture and practical skills training were essential to the significant results and participants’ satisfaction. Conclusions EEG workshops are a great example of combined theoretical and practical training which supports not only the knowledge improvement, but also the practical skills and teamwork experience for future healthcare professionals.